Study of Supra Orbital Notch and Foramen in Adult and Foetal Human Skulls - S.R. Londhe; A.S. Jadhav; A.G. Gosavi (Al Ameen Medical College, 2011)
Background: We aimed to correlate anatomic variation of supra orbital notch, foramen, and incomplete foramen in adult and foetal human skulls for age related difference. Observation: The present study was done on 101 human adult skulls and 59 foetal skulls, to observe the various combinations of supra orbital notch, foramen, incomplete foramen and absence of these features. Result: 9 types of combinations were observed in adult skulls & 8 types of combinations were observed in foetal skulls amongst notch, foramen, incomplete foramen & absence of these features. The difference between incidence of foramen was significant in adult skulls (p<0.05) .percentage of notch was higher in adult 29% as well as foetal skulls 30% than other features. Absence of all the features (notch, foramen and incomplete foramen) were not seen in adult skull but were observed in 6.77% of foetal skulls. Conclusion: All features that is notch, foramen and incomplete foramen was present since 4th lunar month of foetal age in foetal skulls so there was no correlation found in adult and foetal skulls features.